Kadar Glukosa Darah Penderita Tuberkulosis Paru dengan Bakteri Tahan Asam Positif - Suharyati Suharyati; S.Y Didik Widiyanto (Poltekkes Kemenkes Semarang, 2019)
Pulmonary Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, Diabetes Mellitus is one of the most common risk factors in pulmonary tuberculosis patients. Pulmonary TB - DM is more severe and chronic than non-diabetic, which can lead to increased susceptibility to tuberculosis bacteria and longer treatment times. Purpose paper’s is knowing the picture of blood glucose in positive pulmonary tuberculosis patients in UP3 Kebumen. The research conducted included descriptive research type. The population of this study were all pulmonary tuberculosis patients with positive smear in UP3 Kebumen in 2017. The sample used was 100 samples, 6 samples had blood glukosa levels ≥ 200 mg / dl, and as many as 4 people blood glukosa levels between 150 - 199 mg / dl. And most have blood glukosa levels between 70 - 149 mg/dl. Pulmonary TB sufferers in UP3 Kebumen are only a few who suffer from Diabetes.